POTASSIUM FERTILIZATION, ROOT MORPHOLOGY AND POTASSIUM ABSORPTION BY SOYBEAN - Rosolem, Ciro Antonio [UNESP]; Rossetto, CAV; Fernandes, Dirceu Maximino [UNESP]; ISHIMURA, I (Marcel Dekker Inc, 1993)
A greenhouse experiment studied the effect of potassium fertilization on soybean (Glycine max L. Merrill) root morphology and on K absorption by six soybean cultivars of different maturation groups and growth habits. The Plants were grown up to 70 days after plant emergence, in pots containing 6.0 kg of soil. In the absence of K, no significant difference in K absorption was observed among the cultivars or in root length and surface, but root mean radius was correlated to K absorption. Differences in K absorption were not associated with root characteristics in the presence of K fertilization. Physiological adjustments in K uptake, as well as K availability in the soil, were more important in soybean nutrition than were morphological adjustments in the root system. The results were not associated with plant growth habit or with maturation group.